Contextualization of science knowledge: a case study of Malaysian and Nigerian serving and pre-service teachers - Oloruntegbe, Kunle Oke; Alam, Gazi Mahabubul; Syed Zamri, Sharifat Norul Akmar; Okwun, Christopher Kalu; Rabby, Talukder Golam; Kareem, Salami Dada (Academic Journals, 2011)
This study was meant to ascertain how well Malaysian and Nigerian university science education undergraduates and their counterparts (already on the field) contextualize science concepts they are learning or have learned and how well they can help the students they teach connect science with reallife in their teaching. The designs employed in the study were survey and causal comparative. The sample consisted of 240 subjects, 120 from each country drawn from serving and pre-service teachers from Malaysia and Nigeria using stratified sampling technique. Two research questions were raised to guide the study and two hypotheses formulated for testing. A validated instrument labeled contextualization of science knowledge was used for data collection. The psychometric properties and the reliability coefficient of the test were determined for content and construct validity through a pilot study. The instrument was administered and the data collected were analyzed using t-test. The findings are that: a large proportion of the respondents could not contextualize science since the total mean scores of the entire sample are less than half, there was a significant difference in the contextualization of science knowledge among the undergraduates with the Malaysian sample performing better and no significant difference among the serving science teachers.